(untitled) (TAMADDUN NURI JURNALI, 2024)
This article introduces the concept of "educational propaganda," which has not yet been incorporated into the scientific discourse of the field of spiritual studies. It discusses its definition, description, essence, and content, as well as its relationship with other types of propaganda and agitation, and its significance in social life. The relevance and necessity of educational propaganda for the realization of the goals related to the spiritual domain in the development strategy of the New Uzbekistan are also substantiated.